An Integer Linear Programming approach to the Time-constrained Vehicle Routing Problem with Time-windows - Lopes, M. J.; Godinho, M. T. (7th International Symposium on Combinatorial Optimization (ISCO 2022), 2022)
We study a problem arising in home healthcare nursing. Organizing home visits to patients involves features of various OR problems, namely scheduling, rostering and routing. In this work, we address the routing problem, modeled as a Timeconstrained Vehicle Routing Problem with Time Windows (TCVRPTW). An integer linear programming formulation of the TCVRPTW is introduced. Preliminary computational results will be presented at the talk.